Probiotic in Animals - Cid Rigobelo, Everlon (IntechOpen, 2012)
Over the last few decades the prevalence of studies about probiotics strains has dramatically grown in most regions of the world. The use of probiotics strains in animals production may reduce several problems caused by antibiotics therapy, growth promoter and problems from inadequate management. Probiotics are specific strains of microorganisms, which when served to human or animals in proper amount, have a beneficial effect, improving health or reducing risk of get sick. This book provides the maximum of information for all that need them trying with this to help many people at worldwide.